Managing the high-producing herd. III.Producing high quality milk - John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1988)
Progress in the dairy industry over the past 30 yr can be defined as a movement toward fewer farms, more cows per farm, fewer total cows, more milk per cow, a gradual decline in total annual milk production from 1950 through 1975 followed by a sharp increase through 1985, a decrease in per capita consumption, and an increase in milk quality.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Milk; Milk production